Strategic dimensions of product development between the privacy of small and medium enterprises and sustainable development requirements - زموري, كمال; صكري, أيوب (Finance and Business Economies Review, 2019)
This study aims to shed light on product development activity in small and medium enterprises (SMEs) within the context and challenges of sustainable development. The diagnosis of this activity is done in accordance with the different specificities and obstacles facing this kind of enterprises. The findings of the research point out the importance of integrating the different dimensions of sustainable development by small and medium innovative enterprises. Many innovative strategic options that are a source of competitive advantage are open to these enterprises. New green products, digital and Nano industries are good alternatives.